Comparative morphological and anatomical analysis of Thymus serpyllum L., gathered in different parts of Karaganda region - Оrazbayeva, P.Z.; Ishmuratova, М.Yu.; Skalicka-Wozniak, K.; Loseva, I.V.; Ivasenko, S.А. (Publ.KarSU, 2018)
At the article the results of comparative morphological and anatomical analysis of herb Thymus serpyllum L. are given in article for identification of the main distinctive signs of a species. The raw materials of thyme are gathered in Karkaraly Mountains (Karkaraly region) and at the territory of Korneev forest (Bukhar-Zhirau region). Results of researches have allowed defining that the Thymus serpyllum, collected in different areas of the Karaganda region, is presented by two chemo-types. Chemo-types of Thymus serpyllum have external similarity, however under the influence of various factors of the environment essential differences are determined by the external characteristic of stalks, leaves, inflorescences, a structure and omission of a cup and a nimbus that allows using them for identification of this species. In the course of conducting researches micro diagnostic signs for a leaf Thymus serpyllum are specified and also new signs for a stalk, a scape, a nimbus and a cup of whole raw materials are revealed. Diagnostic signs of morphological structure are form and size of stalk, leaf, degree of omission of cup. Diagnostic sings of anatomical structure for leaf, stalk, cup and nimbus are degree of omission, structures of trichomes and their composition, also presence of crystals of oxalate of calcium in tube of nimbus, essential oil glandular, nipples of outgrowths of cells of epidermis for a leaf of a cup, a nimbus.
Қарағанды облысының əртүрлі аудандарында жиналған Thymus serpyllum L. салыстырмалы морфологиялық жəне анатомиялық талдау
Сравнительный морфологический и анатомический анализ тимьяна ползучего (Thymus serpyllum L.), собранного в разных районах Карагандинской области
Keywords: Thymus serpyllum L.; morphological analysis; anatomical analysis; Karkaraly Mountains; Korneevka forest; chemo-type; comparative investigation; identification; micro-signs